NEGOTIATING THE ROMANIAN QUEST FOR CULTURAL IDENTITY AFTER 1989: BETWEEN AUTHENTICITY AND MIMICRY, SELF AND NEO-COLONIZATION - Paris, Andreea Cristina (European Scientific Journal, ESJ, 2014)
Struggling with a seemingly endless period of transition, of inbetweenness with respect to a possible Western future and its communist past, Romania’s ongoing quest for self-definition cannot free itself from the shadow of colonization. This essay aims at presenting the post-communist Romanian attempt to reinvent its cultural identity and will revolve around Homi Bhabha’s theories of the Third Space and of the necessity of cultural liminality applied to Gabriel Andreescu’s article “Interes national, profil intelectual” (Engish translation: “National Interest, Intellectual Profile”). Andreescu’s dialogue with Octavian Paler and Alexandru Paleologu provides fertile ground for negotiation between the ethnocentrism of conservative intellectuals and the progressive Occidentalism of liberal humanists. Just as postcolonial subjects seek self-definition in shaping myths of authenticity or resorting to mimicry, Romanian intellectuals try to heal a wounded selfesteem either by looking backward to an eulogized past or forward to a civilized and civilizing West, yet only manage to display the scars of subjugation by promoting either self or neo-colonization.